Hubungan Beban Kerja Fisik dengan Keluhan Musculoskeletal Disorders pada Pekerja di Pabrik Sepatu di Nganjuk - Putri, Primalia Sukma (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Objective: to identify the association of workload with musculoskeletal disorders complaints in worker in factory shoes Nganjuk Methods: This article were analitycal observational with cross sectional design. The sample of this study used 34 workers from 60 worker of cutting operator in shoe factory Nganjuk. Data were obtained by distributing questionnaires and observation. Physical workload were assess using SNI 7269:2009 guidelines. Data analyzed using fisher’s exact test and coefficient contingency. Data presented using table of content.Results: The result showed that majority had age under 25 years old with male gender. The analysis showed that physical workload have significant association with musculoskeletal disorders complaints among worker. The result were 75% workers with moderate risk of physical workload have mild complaints about musculoskeletal disorders. While 53,8% workers with light physical workload did not have musculoskeletal disorders complains. the association between physical workload and musculoskeletal disorders complain were medium with 0,452 of coefficient contingency Conclusion: Physical workload have significant association with musculoskeletal disorders complaints among worker or in other word increasing of physical workload would be increase complain of musculoskeletal disorders.